Albumin fusion prolongs the antioxidant and anti-inflammatory activities of thioredoxin in mice with acetaminophen-induced hepatitis - Tanaka, R.; Ishima, Y.; Maeda, H.; Kodama, A.; Nagao, S.; Watanabe, H.; Chuang, Victor; Otagiri, M.; Maruyama, T. (American Chemical Society, 2014)
Overdoses of acetaminophen (APAP) are a major cause of acute liver failure. N-acetylcysteine (NAC) is the standard therapy for the patients with such an overdose because oxidative stress plays an important role in the pathogenesis of APAP-induced hepatitis. However, NAC is not sufficiently efficacious. We previously developed a recombinant human serum albumin (HSA)-thioredoxin 1 (Trx) fusion protein (HSA-Trx), designed to overcome the unfavorable pharmacokinetic and short pharmacological properties of Trx, an endogenous protein with anti-oxidative and anti-inflammatory properties. In this study, we investigated the therapeutic impact of HSA-Trx in mice with APAP-induced hepatitis. The systemic administration of HSA-Trx significantly improved the survival rate of mice treated with a lethal dose of APAP compared with saline. HSA-Trx strongly attenuated plasma transaminases in APAP-induced hepatitis mice compared with HSA or Trx, components of the fusion protein. HSA-Trx also markedly caused a diminution in the histopathological features of hepatic injuries and the number of apoptosis-positive hepatic cells. In addition, an evaluation of oxidative stress markers and plasma cytokine and chemokine levels clearly showed that HSA-Trx significantly improved the breakdown of hepatic redox conditions and inflammation caused by the APAP treatment. HSA-Trx also significantly decreased oxidative and nitrosative/nitrative stress induced by SIN-1 in vitro. Finally, HSA-Trx, but not the NAC treatment at 4 hours after APAP injection, significantly inhibited the elevation in plasma transaminases levels. In conclusion, the findings suggest that HSA-Trx has considerable potential for use as a novel therapeutic agent for APAP-induced hepatitis, due to its long-lasting anti-oxidative and anti-inflammatory effects.